Green bond and economic development: Evidence from Asian and European Countries - Andika Waskito Joyonegoro; Putra Pamungkas; Davin Satriyo Wibowo (Sebelas Maret Business Review, 2023)
This study aims to determine the influence of green bonds on economies in Asian and European countries in 2018-2021. Samples in this study, as many as 37 countries in Asian and European, were determined using the purposive sampling method. This study uses data from various sources such as the World Bank, International Monetary Fund, and United Nations Development Programme. This study is a quantitative study whose analysis uses a regression data panel to test the hypothesis of the use of green bonds on the economies of countries in Asian and European in 2018-2021 using Stata. The results showed that the green bond has a positive and significant impact on the economies of countries in Asian and European as measured by Gross Domestic Product. A country's level of well-being can be compared to the dynamic economic impact of an increase that drives growth in Gross Domestic Product. This study implies that the development of green bonds in Asian and European countries can be allocated to implement projects related to the environment and can help countries transform resources to improve the country's economy. Therefore, it is expected that countries in the Asian and European continents are making progress to develop green bonds further to increase the country's Gross Domestic Product.